1991
DOI: 10.1093/infdis/163.2.400
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection in Chronic Hepatitis B Virus Carriers

Abstract: One hundred eighty-four patients with hepatitis B surface antigen-positive chronic hepatitis were evaluated for antibodies to hepatitis C virus (anti-HCV). Only 11 (8%) of 136 patients with hepatitis B virus (HBV) replication (HBV-DNA-positive in serum) while 7 (35%) of 20 positive for antibody to hepatitis B e antigen (anti-HBe) but HBV-DNA-negative were positive for anti-HCV. By contrast, anti-HCV was never found in 30 anti-HBe-positive "healthy" carriers. Anti-HCV was more frequent in hepatitis D virus (HDV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(80 citation statements)
references
References 8 publications
3
77
0
Order By: Relevance
“…In addition, studies from India have shown a prevalence of HCV of 3%-31.5% in patients with cirrhosis and chronic liver disease (Table 4) [14]. However, clinical studies from southern Europe and the USA have shown a high percentage of HCV infection in patients with cirrhosis [15], which is consistent with our findings.…”
Section: ،٤ ‫ﺍﻟﻌﺪﺩ‬ ‫ﻋﴩ،‬ ‫ﺍﳋﺎﻣﺲ‬ ‫ﺍﳌﺠﻠﺪ‬ ‫ﺍﻟﻌﺎﳌﻴﺔ،‬ ‫ﺍﻟﺼﺤﺔ‬ ‫ﻣﻨsupporting
confidence: 91%
“…In addition, studies from India have shown a prevalence of HCV of 3%-31.5% in patients with cirrhosis and chronic liver disease (Table 4) [14]. However, clinical studies from southern Europe and the USA have shown a high percentage of HCV infection in patients with cirrhosis [15], which is consistent with our findings.…”
Section: ،٤ ‫ﺍﻟﻌﺪﺩ‬ ‫ﻋﴩ،‬ ‫ﺍﳋﺎﻣﺲ‬ ‫ﺍﳌﺠﻠﺪ‬ ‫ﺍﻟﻌﺎﳌﻴﺔ،‬ ‫ﺍﻟﺼﺤﺔ‬ ‫ﻣﻨsupporting
confidence: 91%
“…Clinical observations in HBV endemic areas showed that most of the HBV-HCV dually infected cases have similar HCV RNA levels as in patients with HCV monoinfection but relatively low levels of serum HBV DNA compared with patients with chronic HBV monoinfection [24][25][26][27][28]. In patients with chronic hepatitis B along with HCV superinfection, hepatitis B e antigen (HBeAg) seroconversion and even HBsAg clearance have been documented [29,30].…”
Section: Viral Interactions Between Hbv and Hcv And Their Impact On Tmentioning
confidence: 99%
“…The prevalence of HCV infection in patients with HBV infection has been examined in several studies (62)(63)(64)(65). Interestingly, both clinical and animal studies have shown that HCV might exert a viral interference effect that suppresses or terminates the HBV carrier state (66 -70).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%